Pendekatan Konseling Keluarga sebagai Instrumen Penyelesaian Konflik dalam Hukum Keluarga Islam: (Analisis Normatif Berbasis Psikologi Hukum) (Pusat Riset dan Inovasi Nasional, 2026)
Family conflict is an inherent aspect of marital and domestic life and entails complex legal, psychological, and social implications. In the practice of Islamic family law in Indonesia, the resolution of family disputes remains predominantly litigation-oriented, often resulting in the termination of legal relationships, particularly divorce, without adequate attention to the psychological restoration of the parties involved. This article aims to examine family counseling as an instrument for conflict resolution within Islamic family law through a normative legal research approach grounded in legal psychology. The study employs conceptual and legal-psychological approaches, utilizing primary legal sources such as the Qur’an and classical and contemporary Islamic jurisprudence, as well as secondary sources including scholarly books and academic journal articles on family law and legal psychology. The findings indicate that family counseling possesses strong normative legitimacy within Islamic family law through the principles of iṣlāḥ, the mechanism of ḥakam, and the orientation toward public welfare (maṣlaḥah). From a legal-psychological perspective, conflict resolution that accounts for emotional dimensions and procedural justice proves more effective in enhancing legal acceptance and compliance. The integration of family counseling as a restorative instrument does not replace judicial authority but complements it by strengthening the effectiveness of Islamic family law in addressing contemporary family conflicts in a just, humane, and sustainable manner.